Pengaruh Efektivitas Kayu Manis (Cinnamomum burmannii) dan Bunga Cengkeh (Syzygium aromaticum) sebagai Antiseptik terhadap Pertumbuhan Bakteri Escherichia coli - Siregar, Yemima Stephanie Jernita; Marsaulina, Irnawati (TROPHICO: Tropical Public Health J., 2024)
Unclean hands can transfer Escherichia coli from the body, feces, or other sources to food which when consumed can cause diarrhea. One solution to maintain hand hygiene is the use of natural antiseptic. This study aims to determine the effectiveness of cinnamon and cloves as antiseptics against the growth of Escherichia coli. This study is a quantitative study with a true experimental method with a post-test only control design. Testing the inhibition of Escherichia coli in antiseptic extracts using the Kirby-Bauer test with 3 repetitions. The extracts used were obtained from the maceration process and made into several concentrations, namely 20%, 40%, 60%, 80%, and 100%. The positive controls used were Chloramphenicol Palmitate antibiotics and 70% alcohol antiseptic. The negative control in this study was aquadest. The measurement results after 24 hours showed that concentrations of 20%, 40%, 60%, 80%, and 100% respectively effectively inhibited the growth of Escherichia coli because there were clear zones of 10,067 mm, 10,867 mm, 11,267 mm, 12,833 mm, and 13,4 mm. Data analysis using the Kruskal-wallis test showed p- value was 0,026. This means there is a significant difference in the average diameter of the inhibition zone. Through the Post Hoc Multiple Comparison test, it was found that 20% until 80% concentrations had no significant difference with 70% alcohol antiseptic, p-value > 0,05, but 100% concentration had a significant difference with 70% alcohol antiseptic because it had a p-value= 0,036. Starting from 20% concentration, can replace 70% alcohol antiseptic.